Overrepresentation of elements recognized by TCP-domain transcription factors in the upstream regions of nuclear genes encoding components of the mitochondrial oxidative phosphorylation machinery - Welchen, Elina (2006)
We have observed that a cis-acting regulatory element, known as site II, is overrepresented in the promoters of nuclear genes encoding components of the oxidative phosphorylation (OxPhos) machinery from both Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa). Site II elements have been described in promoters of rice and Arabidopsis proliferating cell nuclear antigen (PCNA) genes (Kosugi et al., 1995; Tre´mousaygue et al., 2003) and are also present in the majority of Arabidopsis genes encoding ribosomal proteins (Tre´mousaygue et al., 2003). Loss-of-function analysis has determined that a pair of site II elements present in the rice PCNA promoter is essential for the expression of a reporter gene in the shoot and root meristems of transgenic tobacco (Nicotiana tabacum; Kosugi et al., 1991, 1995). In fact, a promoter region containing these elements is enough to confer expression in tobacco protoplasts when fused to a minimal promoter (Kosugi et al., 1995). Similar elements in Arabidopsis PCNA-2 produce expression in root primordia and young leaves (Tre´mousaygue et al., 2003). Accordingly, these elements have been implicated in the expression of genes in meristematic tissues and/or proliferating cells. Site II elements are frequently present in more than one copy and found in combination with another motif, known as telo box or internal telomeric repeat due to its similarity to the repeated unit of plant telomeres (Tre´mousaygue et al., 2003)